Terrible victory : First Canadian Army and the Scheldt Estuary campaign, September 13-November 6, 1944 - Zuehlke, Mark (Douglas & McIntyre, 2008)
Mark Zuehlke is an expert at narrating the history of life on the battlefield for the Canadian army during World War II. In Terrible Victory, he provides a soldiers-eye-view account of Canada's bloody liberation of western Holland. Readers are there as soldiers fight in the muddy quagmire, enduring a battle that lasted three weeks and in which 6,000 soldiers perished. Terrible Victory is a powerful story of courage, survival, and skill.